Controlled 3D Carbon Nanotube Structures by Plasma Welding. Issue 13 (17th March 2016) - Ozden, Sehmus; Brunetto, Gustavo; Karthiselva, N. S.; Galvão, Douglas S.; Roy, Ajit; Bakshi, Srinivasa R.; Tiwary, Chandra S.; Ajayan, Pulickel M.
Abstract : 3D interconnected carbon nanotubes (CNTs) are synthesized using an industrially scalable spark plasma technique. At high electric field and elevated temperature under sufficient stress the nanotubes are welded together to form a solid block. The detailed spectroscopic and microscopic analyses show successful welding of the CNTs and formation of interconnected networks. The mechanical characteristics of the 3D CNT block show a high stiffness and yield strength. A full atomistic molecular dynamics simulation elucidates the CNT welding mechanism.